2002
DOI: 10.3191/thermalmedicine.18.33
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Particulate Heating Mediator in RF Capacitive Heating.

Abstract: It was shown that alternative magnetic field is generated around ferromagnetic particles in 8 MHz RF electric field and that heat is generated in ferromagnetic particles due to hysteresis loss by the action of alternative magnetic field ; i. e. the same heat generation mechanism with inductive heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We used ferucarbotran, which is clinically used as a contrast agent for MRI examinations, as a means of expanding the size of the RF‐ablated area in rabbit livers. Ferucarbotran is uniformly distributed throughout the entire liver after administration and the SPIO contained in the agent generates heat in an RF electric field 18–22 . In the present rabbits, the signal intensity in the liver decreased in accordance with the given volume of ferucarbotran and the diminution of intensity was homogeneous in each image slice.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…We used ferucarbotran, which is clinically used as a contrast agent for MRI examinations, as a means of expanding the size of the RF‐ablated area in rabbit livers. Ferucarbotran is uniformly distributed throughout the entire liver after administration and the SPIO contained in the agent generates heat in an RF electric field 18–22 . In the present rabbits, the signal intensity in the liver decreased in accordance with the given volume of ferucarbotran and the diminution of intensity was homogeneous in each image slice.…”
Section: Discussionmentioning
confidence: 44%
“…Ferucarbotran is uniformly distributed throughout the entire liver after administration and the SPIO contained in the agent generates heat in an RF electric field. [18][19][20][21][22] In the present rabbits, the signal intensity in the liver decreased in accordance with the given volume of ferucarbotran and the diminution of intensity was homogeneous in each image slice. These results confirmed that the ferucarbotran had been taken equally into the hepatic parenchyma at 4 h after administration in each of the groups.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation